2022
DOI: 10.1186/s13030-022-00250-5
|View full text |Cite
|
Sign up to set email alerts
|

Global prevalence of chronic fatigue syndrome among long COVID-19 patients: A systematic review and meta-analysis

Abstract: Background Chronic fatigue syndrome is a persistent and debilitating disorder. According to several studies, chronic fatigue syndrome has been identified among recovered COVID-19 patients as the most common symptom of long COVID. The aim of this systematic review and meta-analysis study was to obtain the prevalence of chronic fatigue syndrome in long COVID cases. Methods In this systematic review and meta-analysis, we analysed reported results of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 88 publications
0
15
0
2
Order By: Relevance
“…These symptoms include fatigue, sleep problems, problems thinking, and muscle and joint pain. The high frequency of fatigue has been reported by many researchers (Salari et al, 2022), but the evidence for CFS as a sequela of COVID is limited because many studies do not follow patients long enough to establish a diagnosis of CFS.…”
Section: Discussionmentioning
confidence: 99%
“…These symptoms include fatigue, sleep problems, problems thinking, and muscle and joint pain. The high frequency of fatigue has been reported by many researchers (Salari et al, 2022), but the evidence for CFS as a sequela of COVID is limited because many studies do not follow patients long enough to establish a diagnosis of CFS.…”
Section: Discussionmentioning
confidence: 99%
“…However, neuropathy and myopathy are more prevalent than GBS. For example, one study reported a combined rate of 56.3% among 400 hospitalized COVID-19 patients [ 67 ]. The rate of neuropathic pain can be as high as 2.3% in hospitalized patients with COVID-19.…”
Section: Reviewmentioning
confidence: 99%
“…La fatigue est le symptôme le plus fréquent du syndrome post-COVID-19 [56] . Dans des grandes méta-analyses, elle était rapportée dans 47 [57] et 45 % [58] des cas, respectivement. Elle diminuait significativement à deux ans dans la vaste étude chinoise ayant réévalué une cohorte à ce terme [18] .…”
Section: Symptômes Générauxunclassified